A model of redistribution of dopant in a multilayer structure with changing overgrowth regime - E. L. Pankratov (International Journal of Mathematics for Industry)
In this paper, we analyzed the redistribution of dopants in a multilayer structure during the overgrowing of a doped area. The effect of changing of regimes of overgrowing of the doped area on the redistribution of dopant was analyzed. An analytical approach for analysis of the redistribution of dopant was introduced. The approach makes it possible to take into account the changing parameters of the considered process in space and time together, as well as the nonlinearity of the mass transport.